On the cover of Der Heiduck by Hans Wachenhusen - Chernokozhev, Nikolay (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
This paper seeks to highlight the ways in which the visual image of the cover prepares the imminent reader for their encounter with the work.